2010
DOI: 10.1074/jbc.m109.044297
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Flanking Residues in NGR-to-isoDGR Transition and CD13/Integrin Receptor Switching

Abstract: Various NGR-containing peptides have been exploited for targeted delivery of drugs to CD13-positive tumor neovasculature. Recent studies have shown that compounds containing this motif can rapidly deamidate and generate isoaspartate-glycine-arginine (isoDGR), a ligand of ␣v␤3-integrin that can be also exploited for drug delivery to tumors. We have investigated the role of NGR and isoDGR peptide scaffolds on their biochemical and biological properties. Peptides containing the cyclic CNGRC sequence could bind CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(112 citation statements)
references
References 37 publications
0
110
0
2
Order By: Relevance
“…3B). Competitive binding experiments, performed either with the isoDGR peptide capable to bind the RGD binding pocket of integrins (12) or with the control ARA peptide, showed that the isoDGR peptide could abolish the binding of oxidized-aged Cp to the ␣v␤6 integrin (Student's t test, p Ͻ 0.0001) (Fig. 3C), supporting the role of Cp NGR deamidation in the acquisition of binding activity after aging.…”
Section: Accelerated Aging Of Cp Under Oxidative Conditions Causesmentioning
confidence: 81%
“…3B). Competitive binding experiments, performed either with the isoDGR peptide capable to bind the RGD binding pocket of integrins (12) or with the control ARA peptide, showed that the isoDGR peptide could abolish the binding of oxidized-aged Cp to the ␣v␤6 integrin (Student's t test, p Ͻ 0.0001) (Fig. 3C), supporting the role of Cp NGR deamidation in the acquisition of binding activity after aging.…”
Section: Accelerated Aging Of Cp Under Oxidative Conditions Causesmentioning
confidence: 81%
“…Cyclic peptides of different ring sizes (15 < n < 18 atoms) were designed based on previous studies. 13,19,20 The smallest ring size (n=15) is that of 3, (2)) were prepared that were successfully applied previously for drug targeting. 33,34 An alternative synthetic route for 1 is proposed here.…”
Section: Discussionmentioning
confidence: 99%
“…43 However, the receptor recognition of isoDGR peptides highly depends on their structure. 13,44 Our objective was to evaluate the 3D structure, the chemo-stability as well as the in vitro interaction of these peptide models. For such study, cell adhesion was monitored as one of the most…”
Section: Cyclic Ngr-peptides Effect On Cell Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern of expression may due to the fact that during tumor progression endothelial cells and pericytes are differently exposed or susceptible to the angiogenic factors known to regulate CD13. 23 To investigate the interaction between the CNGRCG peptide and CD13 in vivo, the CNGRCGVRSSSRTPSDKY peptide, corresponding to the 17 N-terminal amino acids of the NGR-TNF, was conjugated to quantum dots (hereafter reported as NGR-Qd) 24 and injected in 9 weeks old RIP1-Tag2 mice, during the angiogenic switch stage. Specimens of fresh pancreas were then analyzed by ex vivo whole mount histology.…”
Section: Identification and Localization Of Cd13mentioning
confidence: 99%